APLIKASI MODEL SOCIAL COGNITIVE CAREER THEORY UNTUK MEMPREDIKSI NIAT MAHASISWA BEKERJA SEBAGAI AKUNTAN PUBLIK - Gunawan, Vania Pradipta; Yuliati, Retno (Jurusan Akuntansi Politeknik Negeri Bandung, 2019)
Abstract: The purpose of this research is to examine thesocial cognitive career theory (SCCT) model (Lent, Brown, & Hackett, 1994) which is composed of self efficacy and outcome expectation to predict university students’ intention to work as public accountant. To our best knowledge, this is the first research to examine SCCT model in accounting field; which is done prior and after the respondents take auditing course in university. Data from 234 respondents prior to taking auditing course and 215 respondents after taking auditing course from three universities in Jabodetabek area were taken and analysed using Structural Equation Modeling (SEM). It can be inferred that: (a) the correlation between self-efficacy and university students’ intention to be public accountant is stronger after taking auditing course; (b) the correlation outcome expectation and intention to work as public accountant is not significant both prior to and after taking auditing course;(c) the correlation between self-efficacy and outcome expectation is significant only on respondents after taking auditing course. The limitations in this research are the data was taken prior to and after taking Auditing 1 course (prior to taking Auditing 2) and all respondents are from renowned university in major cities. The result of this research is expected to increase the effectiveness of auditing courses to develop university students’ competence and confidence to achieve their career as public accountant.Keywords:social cognitive career theory, self-efficacy, outcome expectation, public accountant career